Ornamental Traits and Sensory Analysis of ‘Biquinho Vermelha’ Pepper Treated with Paclobutrazol - Beatriz R. Morales; Lucas C. Costa; Marta R. Verruma-Bernardi; Josiane Rodrigues; Fernando C. Sala; Fernando L. Finger; Christiane F. M. França (Agronomy)
This study investigated the impact of paclobutrazol (PBZ) concentrations and application protocols on ornamental quality and consumer preference. PBZ was applied at five concentrations using three different protocols: drench at transplanting, drench 30 days after transplanting, and immersion. At commercial maturity, plants were assessed based on growth parameters related to height, canopy structure, fruit and leaf characteristics, and sensory attributes. The results indicated that PBZ treatments led to darker green leaves and, in general, the drench method, regardless of time application, was more effective in modulating plant growth compared to the immersion protocol. Conversely, the sensory analysis showed a greater preference among evaluators for plants treated with PBZ at 2.5 and 5 mg L−1 via drench at 30 days after transplanting (D30DAT) or through immersion (IM), even though IM was not associated with any of the ornamental quality parameters evaluated. Likewise, the application of PBZ by drench during transplanting is not recommended as the plants showed a reduced number and size of fruits, which affected the ornamental value of the plants and global preference. Therefore, PBZ applied by D30DAT at concentrations of 2.5 and 5 mg L−1 produced ‘Biquinho Vermelha’ pepper plants with attractive ornamental characteristics; and thereby, should be considered an alternative method for producers of potted ornamental plants.